The Relationship between Response Inconsistency Due to Item Wording and Some Variable - Abdelhafez Al-Shayeb (My University, 2009)
The study aimed at determining the relationship between the response inconsistency due to item wording in one hand and the respondent age, gender, Arabic language score in the general secondary certificate exam as an indicator of reading comprehension, and the grade point average as an indicator of achievement. A scale of attitudes towards mathematics was used to collect data from (462) males and females students from different ages and majors in Al al-Bayt University in Jordan. The results revealed a significant mean score differences due to item wording on both sub-scales in favor of the positively worded items. However, it has been found that the internal consistency of the positively-worded items is higher than the internal consistency of the negatively-worded items. Moreover, a relationship has been revealed between response inconsistency and the Arabic language scores in the general secondary certificate exam as an indicator of reading comprehension, as well as the grade point average as an indicator of achievement. Keywords: response inconsistency, item wording, self-report measures, internal consistency.

استهدفت هذه الدراسة الكشف عن العلاقة بين عدم اتساق الاستجابة الناتج عن صياغة الفقرة ومتغيّرات عمر المستجيب وجنسه وعلامته في مادة اللغة العربية في امتحان شهادة الدراسة الثانوية العامة كمؤشر على الاستيعاب القرائي، ومعدّله التراكمي في الجامعة كمؤشر على التحصيل الدراسي. وقد تم جمع البيانات اللازمة عن أفراد الدراسة من خلال تطبيق مقياس الاتجاهات نحو الرياضيات والذي يشتمل على بُعدين اثنين هما تقدير الصعوبة والميل والقيمة الشخصية على عيّنة مكوّنة من (462) طالباً وطالبة من مختلف الأعمار والتخصصات من طلبة جامعة آل البيت في الأردن. وقد كشف التحليل عن وجود فروق ذات دلالة إحصائية بين متوسط استجابات أفراد الدراسة للفقرات الإيجابية والفقرات السلبية على كل بُعد من بُعدي المقياس ولصالح الفقرات الإيجابية. وتبيّن أيضاً أن معامل الاتساق الداخلي للجزء المكوّن من الفقرات الإيجابية أكبر منه بالنسبة للجزء المكوّن من الفقرات السلبية. كما تبيّن كذلك وجود علاقة ببين الفروق في استجابات الأفراد للفقرات الإيجابية والفقرات السلبية في المقياس نفسه وكل من علامة الطالب في اللغة العربية في امتحان شهادة الدراسة الثانوية العامة كمؤشر على الاستيعاب القرائي لدى الطالب من جهة، ومعدّله التراكمي في الجامعة كمؤشر على التحصيل من جهة ثانية. الكلمات المفتاحية: عدم اتساق الاستجابة، صياغة الفقرة، مقاييس التقدير الذاتي، الاتساق الداخلي.
العلاقة بين عدم اتساق الاستجابة الناتج عن صياغة الفقرة وبعض المتغيّرات